Nanoporous Iridium Nanosheets for Polymer Electrolyte Membrane Electrolysis - Chatterjee, Swarnendu; Peng, Xiong; Intikhab, Saad; Zeng, Guosong; Kariuki, Nancy N.; Myers, Deborah J.; Danilovic, Nemanja; Snyder, Joshua (Advanced energy materials, 2021)
The growth of the hydrogen economy is predicated on advancements in electrochemical energy technologies, with water electrolysis as a key component to the technological portfolio. Much of the focus on anode catalyst development for polymer electrolyte membrane water electrolyzers (PEMWE) is centered on activity as controlled by compositional and morphological impacts on reactant/intermediate/product adsorption. However, the effectiveness of this strategy is found to be limited upon integration of these materials into PEMWE membrane electrode assemblies (MEA). Regardless of catalyst activity, the combination of electrode inhomogeneity, ionomer integration, and high density of oxide–oxide interfaces yields significant performance losses associated with poor catalytic electrode conductivity. Here many of these limitations are addressed through the development of a unique catalyst morphology composed of nanoporous Ir nanosheets (npIrx‐NS) that exhibit high catalytic activity for the anodic oxygen evolution reaction and superior electrode electronic conductivity in comparison to a commercial IrO2 nanoparticle catalyst. The utility of the npIrx‐NS is demonstrated through incorporation into PEMWE MEAs where their performance exceeds that of commercial catalyst coated membranes at loadings as low as 0.06 mgIr cm−2 while exhibiting a negligible loss in performance following 50 000 accelerated stress test cycles. Nanoporous Ir nanosheets (npIrx‐NS) are a unique anode catalyst combining high surface‐to‐volume and interconnected metallic backbone to yield enhanced mass activities and reduced ohmic losses in water electrolyzers. The utility of npIrx‐NS is demonstrated by enhanced performance at low loadings while exhibiting negligible loss in performance following 50 000 accelerated stress test cycles.